2005
DOI: 10.1080/08035250410023746
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of exclusive breastfeeding during hospital stay in the area of Athens, Greece

Abstract: Exclusive breastfeeding during hospital stay in the area of Athens is low. Demand feeding and rooming-in positively influence exclusive breastfeeding initiation, while caesarean section and information by mass media have a negative impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 17 publications
3
19
1
1
Order By: Relevance
“…Similar to the findings of Hwang’s study (22), in our study, cesarean sectioned mothers were less successful in breastfeeding duration than those who had normal delivery. Our findings were also consistent with the findings of Throfilofiannakou et al in Greece (23), Chandrashekher et al in Western Nepal (24), Batal et al in Lebanon (25), Mikiel-Kostyra et al in Poland (26), and Pechlivoni et al in Athens-Greece (27). Although, in studies conducted by Escamilla in Mexico (28), Lathauwer (29), and Pattle (30), the type of delivery was effective on breastfeeding period, which can be because of better mother outcome after normal delivery vs. cesarean section.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of Hwang’s study (22), in our study, cesarean sectioned mothers were less successful in breastfeeding duration than those who had normal delivery. Our findings were also consistent with the findings of Throfilofiannakou et al in Greece (23), Chandrashekher et al in Western Nepal (24), Batal et al in Lebanon (25), Mikiel-Kostyra et al in Poland (26), and Pechlivoni et al in Athens-Greece (27). Although, in studies conducted by Escamilla in Mexico (28), Lathauwer (29), and Pattle (30), the type of delivery was effective on breastfeeding period, which can be because of better mother outcome after normal delivery vs. cesarean section.…”
Section: Discussionsupporting
confidence: 92%
“…A related study that took place in Greece looked for factors that influenced breastfeeding similar to the current study. Interestingly, their study identified a significantly decreased association with first-time mothers exclusively breastfeeding on discharge (OR = 0.66; 95% CI = 0.51-0.84) [16], which is in disagreement with the current study (OR = 2.09; 95% CI = 1.52, 2.87). This difference could be due to the different cultures studied in relation to breastfeeding.…”
Section: Discussioncontrasting
confidence: 99%
“…From a previous study we know that all Danish NICUs offered the mothers rooming-in some days before discharge, and in 42% of the NICUs the mother could have a bed in the NICU when she was discharged from maternity ward [2]. Therefore, we still lack knowledge of whether or not rooming-in for the infant’s whole hospitalisation period (defined as sleeping together) is associated with breastfeeding success for preterm infants, just as it is for non-preterm infants [19]. A Swedish study found that mothers separated from their newborn infants experienced emotional strain and anxiety; they felt like they were outsiders, and experienced a lack of control when the infant was admitted to neonatal intensive care [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not designed to give definitive answers to whether or not these practices promote breastfeeding and, furthermore, it should be emphasized that there may be other benefits of these practices for the mother-infant relationship than that of promoting breastfeeding. Skin-to-skin contact has previously been positively associated with breastfeeding preterm and non-preterm infants [15], [16], [17], [43], but only one study of preterm infants demonstrated that the initiation of continuous skin-to-skin contact before 24 hours postpartum was positively associated with exclusive breastfeeding at six months of age [19]. Most of the infants (98%) in the present study had skin-to-skin contact during the NICU stay, and it seems that even if 42% of the mothers were not able to have early skin-to-skin contact with their preterm infants this was not an essential barrier to the establishment of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation